Marguerite Bourgeoys et Montréal, 1640-1665 - Simpson, Patricia, 1937- (McGill-Queen's studies in the history of religion., 1999)
St Marguerite Bourgeoys (1620-1700), canonized in 1982, is a key figure in Canadian and religious history as a founder of Montreal and of the international order the Congrégation de Notre-Dame de Montréal, one of the first uncloistered religious communities of women. Patricia Simpson goes behind the mist of myth and hagiography surrounding Marguerite Bourgeoys to reveal her true character. Marguerite Bourgeoys et Montréal documents her life in France and in the struggling settlement of Ville-Marie - present-day Montreal - placing her life within the larger historical context of the time and highlighting the role of women in society and the church.